Design and implementation of a Nonlinear Control System by multivariable sliding modes applied to a 2DOF Translational Robotic Manipulator - Rodriguez Bustinza, Ricardo (2001)
The present work deals with the trajectory control of a 2 DOF (Degrees-of-Freedoms) multivariable translational robotic manipulator that consists of a carriage driven by a pulley and an articulated link in the CG (center of gravity) of said carriage. . Such process will be controlled through the sliding mode control technique. The control action is aimed at controlling the translational movement of the mobile and the angular movement of the rod, which is free to rotate in both directions. The goals imposed for this work are: modeling of the process and simulation of the system with the law of control by sliding modes. This control law employs discontinuous nonlinear feedback on a given surface. belongs to the state space of the system. If a state trajectory originating from this surface (in response to the natural behavior of open-loop system dynamics) attempts to deviate from it, then a control force acts to prevent such a deviation. Simulation studies will demonstrate that designed control signals can efficiently cause outputs to follow arbitrary reference trajectories.